KEMAMPUAN MENULIS KATA DALAM TULISAN ARAB-MELAYU SISWA SDN 021 PEKANBARU - Hasnah Faizah; Nabila Nabila; Niken Aulia; Ayu Lestari (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This study aims to measure the ability of elementary school students to write words in Arabic-Malay script as one of the competencies that must be mastered in the local content subject of Riau Malay Culture. The ability to write Arabic-Malay writing is important to learn at the elementary school level as an effort to recognize and preserve the existence of Arabic-Malay writing as a cultural heritage of the Riau Malay natural community. This research was conducted at SDN 021 Pekanbaru in grade 3 with a total of 28 students. The research was carried out on November 22, 2022. The data collection technique in this study used a test technique. Data analysis was performed using scoring techniques, percentages, and categorizing research data (low, medium, and high). The results showed that the ability to write open monosyllabic words into Arabic-Malay script was in the high category with a percentage of 50.00%.